Natural and industrial origin reinforced LM6 aluminum matrix composite materials – a comparative study - Fuhaid, Mutlag Sh.; Maleque, Md. Abdul; Venkat, Murali; Abd. Rahman, Mohamed (AIP Publishing, 2021)
Aluminum alloy is one of the most common and basic metallic alloys used as a matrix phase of composite material due to its higher strength-to-weight ratio, enhanced thermal conductivity, excellent stiffness as well as wear and corrosion resistance properties. Aluminum based composite materials have become an obvious entry into many industries such as automobile, aerospace, construction, household appliances, and food packaging industries. The common reinforcement materials to fabricate aluminum composites are aluminum oxide, silicon carbide, boron carbide, boron nitride, titanium carbide, tungsten carbide and titanium diboride. However, most of the ceramic based reinforcement materials are expensive and not environmentally or human friendly. Recent research has been tailored to the use of industrial waste as a reinforcement for aluminum composites such as slag, red mud, fly ash, arc furnace dust and waste glass. The use of natural materials such as glass and marble waste is promising because they are cheaper than conventional ceramic reinforcement and they also might enhance the properties of the composite. Therefore, this study aims to make a comparative study for mechanical and physical experimental work on using 5% marble wastes (MW) as a natural reinforcement and 5% graphene oxide (GO) as an industrial origin reinforcement in LM6 aluminum composites. Mechanical testing methods like tensile test, hardness and impact test are conducted. Elemental analysis and microstructure properties using optical microscope and SEM and EDS to study the homogeneity of particles distributions and type of fracture surface. The results showed the superiority of GO over MW where the Ultimate Tensile Strength (UTS) increased by 45% in GO, while 16% in MW. The value of Rockwell hardness of both composites materials was obtained which is more than doubled than that of LM6 alloy material. The Impact test rate increased in LM6/MW by 19% while approximately LM6/GO 36%. Marble waste and graphene oxide particles were homogeneously distributed in the matrix, and a strong bond was formed between the aluminum and the reinforced partition.